ANALISIS KINERJA RUMAH SAKIT DENGAN MENGGUNAKAN METODE BALANCED SCORECARD DI RUMAH SAKIT BHAYANGKARA TK III AMBON - Christina Sososutiksno (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to analyze the performance of Bhayangkara Hospital TK III Ambon using the balanced scorecard method from a financial perpective, a customer perspective, an internal business process perspective, and a growth and learning perspective. This research is a quantitative descriptive analysis research. Data collection techniques in this study were documentation, questionnaires, and interviews. The result of the study are the financial perspective is measured by 3 ratios, namely the economic ratio is categorized as balanced economy, the efficiency ratio is categorized as inefficient, and the effectiveness ratio is categorized as effective. Internal business for ALOS, BOR, TOI, and BTO are categorized as not ideal, GDR and NDR is categorized as ideal, and growth and learning perspectives through questionnaires are categorized as good.Key words: Performance, Hospital, Balanced Scorecard.